Decisions Regarding Newborn Feeding by Latina Mothers. (February 2018) - Jones, Amy; Reller, Lara; Knowles, James; Lin, Feng-Chang; Lohr, Jacob
This study examined the factors that influence Latina mothers' decisions to initiate breastfeeding, formula feeding, or both, and when a given neonatal feeding method is decided, in order to assess the optimum time for healthcare providers to discuss nutrition decisions. A Spanish-speaking health care provider orally administered a 24-question survey to self-identified Latina mothers in the Newborn Nursery at North Carolina Children's Hospital after delivery. A total of 152 Latina mothers, aged 17 to 43 years, were interviewed from September 2014 to September 2015. Three decisive factors resulted from multivariate analysis regarding a participant's decision to exclusively breastfeed: age (27.3 years or younger); deciding about feeding method before pregnancy; and believing that exclusively breastfeeding is best for an infant's growth and development. Overall, 95% of Latina mothers made their decision regarding their infant's nutrition before delivery. Newborn nurseries have trended toward the allocation of substantial resources to the mission of enhancing the likelihood of breastfeeding initiation and success in the newborn period. Perhaps a reallocation of some of these resources for educational interventions earlier in pregnancy should be considered.